2009
DOI: 10.1177/1367493509337440
|View full text |Cite
|
Sign up to set email alerts
|

A self-harm training needs assessment of school nurses

Abstract: Self-harm is acknowledged to be increasing and is especially prevalent in young people. School nurses are central to adolescent mental health, delivering initial and sustained intervention. However, few studies have considered their experiences and training needs in fulfilling this role. This training needs assessment explored the self-harm training needs of school nurses within one UK primary care trust by utilizing questionnaires and interviews developed specifically for the study. School nurses felt frustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…The results of our study are in line with other studies aiming at a more positive attitude on the part of staff towards self-harm patients. Several studies revealed that training professionals leads to a better understanding of self-harming behaviour and a more positive attitude towards these patients [25-27]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are in line with other studies aiming at a more positive attitude on the part of staff towards self-harm patients. Several studies revealed that training professionals leads to a better understanding of self-harming behaviour and a more positive attitude towards these patients [25-27]. …”
Section: Discussionmentioning
confidence: 99%
“…They expressed the need for more education on the issue, as in earlier studies. [23][24][25][26] One ethical challenge for the participants was the documentation of mental health problems in the health record. This was because of the sensitivity of this issue and also because the health record prioritised information about physical health.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to S. Allen (2007), effective education for all those working with people who self-harm is needed and necessary, and in addition, there is a lack of basic knowledge of self-harm among health-care students (Law et al, 2009). Moreover, McDonald (2006 stated that school nurses are particularly in need of education, including theoretical knowledge and practical approaches concerning self-mutilation and self-harm (Cooke & James, 2009). Furthermore, Advanced Practical Nurses in all specialties are in need of additional education concerning self-harm among adolescents (Tusaie, Acierto, Murray, Fitzgerald, & Chiu, 2009).…”
Section: Caring For Persons Who Self-harm or Self-mutilatementioning
confidence: 99%